RELATION BETWEEN GRAPHIC DESIGN AND MYTHOLOGY - V, Niharika; Aparna, Wudali Kruthica; Adipudi, Shria; Banerjee, Kingshuk; Varma, Vyshnavi; Solanki , Chaitanya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Graphic design plays a huge role in our lives, starting from logos to animations to comics. It is very hard for us to imagine a world without graphic design. Graphic design dates back to the prehistoric time of cave paintings and now as digital media. It is a part of visual communication which helps us to deliver a specific message to the target audience using art. Mythology is the ancient information that our older generations have been passing down to the next generation for us to understand our culture, belief, literature and world. Using Graphic design as a medium to enlighten people about our mythology is increasing and helps our younger generation to know about our culture better, but this also has its own set of disadvantages. This paper is a Systematic Literature Review (SLR) on how Mythology affects Graphic Design – Comics, Animations, Character Making etc and how these stories have been reimagined, retold in today's world. This analysis was started off with a sample of 100 papers which included books, research papers and articles out of which 20 papers were deemed eligible for the research. The aim of this paper was to find out how different mythologies have affected today’s graphic design. The findings of this review can help the future researchers to understand how mythology affects graphic design and vice-versa. The research was accomplished using the databases from Taylor and Francis, SAARC Culture etc. The review concludes with findings on aspects of mythology, graphic design, change in time and how the socio-economic prevalence has changed the way the stories and characters from mythology have been portrayed in today’s world and the way this change is received by the younger audience. Thorough research is required for going in depth on any topic for detailed aspects.